ANALISIS YURIDIS HUKUMAN PIDANA KUMULATIF KURIR NARKOTIKA DITINJAU DARI UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA (Analisis Putusan Mahkamah Agung Nomor 910 K/Pid.Sus/2020) - Nurza Ismam, Riza Fauzi; Purba, Nelvita; Akhyar, Adil (Jurnal Ilmiah METADATA, 2021)
Imposing a person who has committed a criminal act is a very important part of realizing the criminal justice system. The formulation of the problem in this thesis is how the provisions of the cumulative criminal law in life imprisonment and fines for narcotics couriers who commit evil conspiracy (samenspanning), how to apply cumulative criminal sanctions to life imprisonment and fines for narcotics couriers who commit criminal conspiracy (samenspanning), how to consider judges in verifying narcotics couriers as perpetrators of criminal conspiracy (samenspanning) in narcotics crimes in the Supreme Court decision Number 910 K / Pid.Sus / 2020. This type of research is juridical normative, namely research based on law. The data analysis was carried out qualitatively, which is a form of analysis that does not rely on numbers but on sentences. The conclusion in this paper is carried out using deductive-inductive thinking logic, which is done with the theory used as a starting point for conducting research. The results showed that the cumulative criminal law arrangements for life imprisonment and fines for narcotics couriers who commit criminal conspiracy (samenspanning) are regulated in Article 112 paragraph (1) in conjunction with Article 132 paragraph (1) of Law of the Republic of Indonesia No. 35 of 2009 concerning Narcotics, namely a criminal act of conspiracy without rights or against the law of planting, maintaining. The application of cumulative criminal sanctions in life imprisonment and fines for narcotics couriers who commit evil consensus (samenspanning) is in accordance with the decision of the Stabat District Court, namely Defendant I was sentenced to life imprisonment but at the level of cassation filed by Defendant II, the sentence against Defendant II was changed to 12 years imprisonment and a fine because Defendant II was only a courier, not a narcotics owner in this case. The judge's consideration in verifying the narcotics courier as the perpetrator of a criminal conspiracy (samenspanning) in the narcotics crime was because there was no justification and excuse for the act committed by the defendant.